2008
DOI: 10.1021/jo702327m
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional Tetrazolic Thioethers through Electrooxidative/Michael-Type Sequential Reactions of 1,2- and 1,4-Dihydroxybenzenes with 1-Phenyl-5-mercaptotetrazole

Abstract: In the presence of 1-phenyl-5-mercaptotetrazole as a nucleophile, electrochemical oxidations of 1,2- and 1,4-dihydroxybenzenes have been investigated in aqueous solution using cyclic voltammetry and controlled-potential coulometry. The voltammetric results indicate that an electrooxidative/Michael-type sequential reaction occurs between the mercaptide anion and the electrochemically generated benzoquinones leading to the corresponding polyfunctional tetrazolic thioethers. The mechanism of electrochemical react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…The results revealed that the quinones derived from catechols participate in a Michael type addition reaction via an EC mechanism converted to the corresponding catechol derivatives. The electrochemical synthesis of various thiocatechol products (Table 2) has been successfully performed at a carbon rod electrode and in an undivided cell with good yields and high purity [18][19][20][21][22][23][24][25][26].…”
Section: C-s Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the quinones derived from catechols participate in a Michael type addition reaction via an EC mechanism converted to the corresponding catechol derivatives. The electrochemical synthesis of various thiocatechol products (Table 2) has been successfully performed at a carbon rod electrode and in an undivided cell with good yields and high purity [18][19][20][21][22][23][24][25][26].…”
Section: C-s Bond Formationmentioning
confidence: 99%
“…Some new C-phosphoniumquinol betaine compounds (23) were synthesized from a conjugated addition reaction of triphenylphosphine (22) to the electrochemically generated obenzoquinone via an EC mechanism (Scheme 6) [34].…”
Section: C-p Bond Formationmentioning
confidence: 99%
“…The precipitated solid was collected by filtration, washed copiously with distilled water and characterized by spectral data and were compared with those reported in the literature. 38,39) The final products (1A-5A, 1B-3B) were obtained purely and no extra purification was needed. 38,39) 4-tert-Butyl-5-(1-phenyl-1H-tetrazol-5-ylthio)benzene-1,2-diol (1A) 39) mp 181-183°C; yield 59%; IR (KBr) cm …”
Section: Methodsmentioning
confidence: 99%
“…1, the compound I derivatives has well-known antiviral and anti-inflammatory properties, 32,33) 1-aryl-thiotetrazolyl acetanilides (II, III) have demonstrated activities as human immunodeficiency virus-1 (HIV-1) non-nucleoside reverse transcriptase inhibitors, [34][35][36] and 1-phenyl-5-arylthiotetrazole (IV) is used as activating reagent in RNA synthesis. 37) Due to a broad spectrum of activities reported in the literature so far, we have prepared a number of catecholthioethers having benzoxazole 38) and tetrazole 39) moieties for evaluating their antimicrobial and antioxidant activities (Chart 1).…”
mentioning
confidence: 99%
“…In addition, they are major raw materials used in a wide range of applications including dyes, light stabilizers, electroplating materials, and antioxidants [1,2]. However, they are highly toxic compounds, with stimulatory effects on the central nervous and respiratory systems.…”
Section: Introductionmentioning
confidence: 99%